Anti-Tick-Bourne Encephalitis IgM Intrathecal Synthesis as a Prediction Marker in Tick-Borne Encephalitis Patients - Piotr Czupryna; Sambor Grygorczuk; Agnieszka Siemieniako-Werszko; Jakub Okrzeja; Justyna Dunaj-Małyszko; Justyna Adamczuk; Sławomir Pancewicz; Joanna Zajkowska; Karolina Narejko; Joanna Oklińska; Gabriela Trojan; Anna Moniuszko-Malinowska (Microorganisms, 2025)
The aim of this study was to evaluate the usefulness of IgM anti-Tick-Borne Encephalitis (anti-TBE) intrathecal synthesis in the diagnosis and prediction of the clinical course of the disease. Thirty-six patients were included in the study (patients reported symptoms such as fever, headache, fatigue, and nausea/vomiting). CRP, White Blood Cells (WBC), pleocytosis, Cerebrospinal Fluid (CSF) protein concentration, CSF albumin concentration, serum IgM, serum IgG, CSF IgM, CSF IgG, IgM Index, IgG Index, and IgG Index/IgM Index ratio were the parameters which were examined in the individuals. An analysis of correlation presented statistical significance between IgM Index and pleocytosis and protein concentration in CSF in the whole group of individuals. IgM Index and IgG Index/IgM Index ratio may be used in the prediction of severity of TBE. The most probable link between the IgM intrathecal production and severity of TBE may be a result of delayed seroconversion to IgG, and therefore not an adequate response to the virus presence.